2019
DOI: 10.22219/jpbi.v5i1.7385
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of biology module based on Stim-HOTS models

Abstract: Based on the needs analysis done, the empowerment of higher-order cognitive skills of the students in Surakarta was not optimal yet. This research addressed to determine and describe the feasibility of biology module which was arranged based on Stimulating Higher-Order Thinking Skills (Stim-HOTS) model. This Research and Development (R&D) involved six expert validators, including material validator, module development validator, language validator, learning instrument validator, and school practitioners. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…Based on the criteria for the effectiveness of teaching materials and supported by the implementation of lesson plans and student activities in learning, it can be concluded that biology teaching materials in the form of excretory system material modules that are integrated with the values of the Al-Qur'an and As-Sunnah are effectively used in the learning process to improve students' cognitive and activeness, psychomotor learning outcomes, and students' IMTAQ scores. According to (Pramesti et al, 2019), modules as independent teaching materials play an important role in the learning process, namely by placing students as learning subjects so that the learning environment created is active learning without depending on the teacher's availability. The module as an evaluation tool can function as a medium for student reflection on the topics they have studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the criteria for the effectiveness of teaching materials and supported by the implementation of lesson plans and student activities in learning, it can be concluded that biology teaching materials in the form of excretory system material modules that are integrated with the values of the Al-Qur'an and As-Sunnah are effectively used in the learning process to improve students' cognitive and activeness, psychomotor learning outcomes, and students' IMTAQ scores. According to (Pramesti et al, 2019), modules as independent teaching materials play an important role in the learning process, namely by placing students as learning subjects so that the learning environment created is active learning without depending on the teacher's availability. The module as an evaluation tool can function as a medium for student reflection on the topics they have studied.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this background and problems, it is necessary to develop biology teaching materials that are integrated with the values of the Al-Qur'an and As-Sunnah to the stage of effectiveness. The development of teaching materials integrated with Al-Qur'an values in reproductive materials has been reported by several researchers previously (Agusti et al, 2019;Pramesti et al, 2019) but there has been no development of integrated teaching materials with Al-Qur'an and As-Sunnah values in excretory system material. Excretory system material is part of biological material which is also full of the values of the Al-Qur'an and As-Sunnah.…”
Section: Introductionmentioning
confidence: 99%
“…Nilai kepraktisan modul yaitu 91,29% dengan kategori sangat valid. Nilai kepraktisan menujukkan bahwa modul peruban lingkungan berbasis ESQ telah memiliki tampilan menarik, meingkatkan motivasi belajar mahasiswa, penyajian materi yang mudah dipahami dan berkaitan dengan kehidupan sehari-hari, memandu diskusi sesama mahasiswa, media untuk peningkatan sikap peduli lingkungan, dapat digunakan secara mandiri oleh mahasiswa, efektif digunakan dalam pembelajaran, meningkatkan keaktifan mahasiswa, baca modul mudah dipahami (Daryanto, 2013;Departemen Pendidikan Nasional, 2008;Heri, 2014;Pramesti et al, 2019;Qadariah, 2022a;Salirawati, 2018).…”
Section: Pembahasanunclassified
“…Uji keefektifan modul berfungsi untuk menilai apakah modul sudah efektif digunakan dalam pembelajaran (Departemen Pendidikan Nasional, 2008;Purwanto et al, 2007;Salirawati, 2018). Keefektifan modul dapat dinilai dari berbagai aspek, contohnya efektif untuk meningkatkan pemahaman mahasiswa, keterampilan komunikasi, keterampilan proses sains, keterampilan kolaborasi, dan keterampilan pemecahan masalah (Hervi & Ristiono, 2021;Khalil et al, 2020;Leasa et al, 2016;Pramesti et al, 2019;Qadariah, 2022a;Rahmadhania et al, n.d.;Serrat et al, 2014).…”
Section: Pembahasanunclassified
“…In order to realize this need, it becomes a must to familiarize students to develop HOTS that can be seen from several aspects such as critical thinking, creative, problem solving, and high level decision making that can be developed in the learning process (Husamah, Fatmawati, & Setyawan, 2018;Pramesti, Sajidan, Dwiastuti, & Setyaningsih, 2019;Ramdiah, Abidinsyah, Royani, & Husamah, 2019;Ramdiah et al, 2018), both in the classroom and in the laboratory (Ghani, Ibrahim, Yahaya, & Surif, 2017;Hugerat & Kortam, 2014;Madhuri, Kantamreddi, & Goteti, 2012;Ramesh & Rao, 2015;Setiawan, Malik, Suhandi, & Permanasari, 2018;Yonata & Nasrudin, 2018), and in assessment activities (Budiman & Jailani, 2014;Ghani et al, 2017;Razmawaty & Othman, 2017;Retnawati, Djidu, Apino, & Anazifa, 2017). The ability to think high according to Brookhart (2010) is at the top of Bloom's cognitive taxonomy.…”
Section: Introductionmentioning
confidence: 99%